An investigation into the cracking of platinum aluminide coated directionally solidified CM247 LC high pressure nozzle guide vanes of an aero engine. (December 2018) - Balam, S.S.K.; Tamilselvi, M.; Mondal, A.K.; Rajendran, R.
Abstract: In service inspection of RT-22 platinum aluminide coated directionally solidified CM247LC high pressure turbine nozzle guide vanes of an aero engine which underwent 134 runs as an assembly set revealed cracking in 23 out of the total 34 vanes(17 pairs). A detailed investigation was launched on one of the cracked vanes which revealed that thermomechanical fatigue was the root cause of the failure. Incipient melting, in addition, was observed in platinum aluminide coating and at the interior of the vanes. A relook at the engine shut down procedure and an operating temperature not exceeding safe maximum limit were recommended to protect the vanes against these degradations. Highlights: High pressure nozzle guide vanes found to be cracked after 134 cycles. Thermomechanical fatigue found to be root cause. Incipient melting observed.